Developing environmental care attitudes among college students through islamic education (IRE) learning with a humanist-contextual approach. Issue 1 (May 2021) - Mardhiah, I; Amaliyah,; Hakam, A; Hadiyanto, A
Abstract: This study aimed to show that religious teaching contributes to preserving the environment. The research illustrates how to build students to do positive things through learning Islamic Education (IRE), which includes empowering a caring attitude towards the environment. It is one of the primary learning outcomes of IRE in higher education. There is a need to determine the competence of IRE learning outcomes, and it is challenging to understand environmental conservation factors from a theological perspective. Therefore, IRE learning should be able to facilitate students to have competence in caring for the environment. This research was a qualitative study using quota and snowball sampling. The subjects were IRE students and lecturers. Data were collected using library literature, questionnaires, and interviews. The results show that empowering a caring attitude towards the environment through IRE can be achieved by; 1) using theological methods that indicate the level of spiritual maturity; 2) psychological approaches that hone students' social maturity; 3) empowering a caring attitude towards the environment using contextual learning that enables students to analyze the facts of environmental preservation and the impact of an environmental crisis from an Islamic perspective. The development of teaching materials and assessment instruments appropriate for IRE learning with a humanist and contextual approach can empower students' environmental care attitudes.